Analisis Kalimat Fakta dan Opini dalam Teks Artikel pada Buku IPS Kelas X SMA Kurikulum Merdeka - Laila Faza Naimah; Rizky Aprilia; Fitriani Nuraisah; Mei Purweni; Asep Purwo Yudi Utomo; Didi Pramono (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
The research we conducted in studying fact and an opinion sentences in articles in the book IPS Kelas X Kurikulum Merdeka, is one part of understanding further what they are and how to study them, and distinguish fact sentences and opinion sentences. The fact sentence itself is a sentence that expresses the real truth and can be proven true, while the opinion sentence is a sentence that expresses an opinion or response from a writer. The purpose of the research we did none other than to fulfill the assignment for the Fundamentals of Syntax course, besides that as material for exploring material related to fact sentences and opinion sentences. This research method is descriptive qualitative. This research will later describe the form of sentences of facts and opinions in the article, the analysis is carried out by looking for sentences that show facts and opinions in an article, the source of the data in this study is articles from the book IPS Kelas X Kurikulum Merdeka. The data collection technique in this study uses the equivalent technique, namely comparing one text with another. The results obtained are being able to distinguish and detail every sentence of fact and opinion in the article. The benefits obtained are better understanding related to this matter and as a reference for further research.